Choice of Alternative Polyadenylation Sites, Mediated by the RNA-Binding Protein Elavl3, Plays a Role in Differentiation of Inhibitory Neuronal Progenitors - Grassi, Elena; Santoro, Roberto; Umbach, Alessandro; Grosso, Anna; Oliviero, Salvatore; Neri, Francesco; Conti, Luciano; Ala, Ugo; Provero, Paolo; DiCunto, Ferdinando; Merlo, Giorgio R. (Frontiers in Cellular Neuroscience, 2019)
Alternative polyadenylation (APA) is a widespread mechanism involving about half of the expressed genes, resulting in varying lengths of the 3'UTR. Variations in length and sequence of the 3’UTR may underlie changes of post-transcriptional processing, localization, miRNA targeting and stability of mRNAs. During embryonic development a large array of mRNAs exhibit APA, with a prevalence of the longer 3’UTR versions in differentiating cells. Little is known about polyA+ site usage during differentiation of mammalian neural progenitors. Here we exploit a model of adherent neural stem (ANS) cells, which homogeneously and efficiently differentiate into GABAergic neurons. RNAseq data shows a global trend towards lengthening of the 3’UTRs during differentiation. Enriched expression of the longer 3’UTR variants of Pes1 and Gng2 was detected in the mouse brain in areas of cortical and subcortical neuronal differentiation, respectively, by two-probes fluorescent in situ hybridization. Among the coding genes upregulated during differentiation of ANS cells we found Elavl3, a neural-specific RNA-binding protein homologous to Drosophila Elav. In the insect, Elav regulates polyA+ site choice while interacting with paused Pol-II promoters. We tested the role of Elavl3 in ANS cells, by silencingElavl3 and observed consistent changes in 3’UTR length and delayed neuronal differentiation. These results indicate that choice of the polyA+ site and lengthening of 3’UTRs is a possible additional mechanism of posttranscriptional RNA modification involved in neuronal differentiation.